Leadership and Leadership Development : Critical Perspectives and Contemporary Approaches - Harrison, D. Christian (Routledge, 2025)
Leadership as a practice, and the development of leaders, has evolved significantly in recent decades, influenced by rapid changes in the business landscape, technology, social norms, and global challenges. The unprecedented disruptions brought about by crises, the increased awareness around diversity, equity, and inclusion, and the rise of new organisational models have all necessitated a rethinking of traditional leadership frameworks. At the same time, the focus on leadership development has shifted, with a greater emphasis on developing skills that foster adaptability, inclusivity, sustainability and resilience.In response to these shifts, this book provides a critical examination of leadership and leadership development, offering new insights and contemporary approaches that reflect the changing needs of organisations and societies. With contributions from leading scholars and practitioners across diverse fields, the 12 chapters in this edited volume present a rich blend of theoretical, empirical, and reflective research. It provides fresh perspectives on leadership development by exploring themes such as diversity and inclusion, sustainability, innovation and resilience.
Keywords: Leadership.; Leadership; Leadership Development; Contemporary Approaches; Complexity; Practice; Research; Management; Organization; elektronické knihy; electronic books